Analisis Seni Sebagai Medium Disrupsi dalam Strategi Visual Mendorong Wacana Sosial di Era Post Truth - Aliyah; Widya Oktary Setiawardhani; Amanda (Pantarei, 2026)
The post-truth era has given rise to an information crisis that blurs the boundaries between facts and opinions andtriggers social and political polarization in the public space. In this context, visual art is present as a medium ofdisruption that is able to intervene in dominant discourse through symbolic strategies, participatory aesthetics, andvisual criticism. This research uses a qualitative-descriptive approach with literature studies and visual semioticanalysis of the works of artists and collectives such as Taring Padi, Banksy, JR, and ruangrupa. The results show thatart not only represents social reality but actively shapes a counter-narrative to disinformation through visuals thatevoke emotions, trigger awareness, and build critical community participation. Visual art in the post-truth era used to be a strategic communication tool that was not only aesthetic but also political and ideological